A Practice‐Based, Clinical Pharmacokinetic Study to Inform Levetiracetam Dosing in Critically Ill Patients Undergoing Continuous Venovenous Hemofiltration (PADRE‐01). Issue 5 (3rd April 2020) - Kalaria, Shamir N.; Armahizer, Michael; McCarthy, Paul; Badjatia, Neeraj; Gobburu, Jogarao V.; Gopalakrishnan, Mathangi
Abstract : Limited data exist on the effect of continuous renal replacement therapy (CRRT) methods on anti‐epileptic drug pharmacokinetics (PK). This prospective practice‐based PK study aims to assess the impact of continuous venovenous hemofiltration (CVVH), a modality of CRRT, on levetiracetam PK in critically ill patients and to derive individualized dosing recommendations. Eleven patients receiving oral or intravenous levetiracetam and CVVH in various intensive care units at a large academic medical center were enrolled to investigate the need for dosing adjustments. Prefilter, postfilter, and ultrafiltrate samples were obtained before dosing, after the completion of the infusion or 1‐hour postoral dose, and up to 6 additional time points postinfusion or postoral administration. Patient‐specific blood and ultrafiltrate flow rates and laboratory values were also collected at the time of sampling. The average sieving coefficient (SC) for levetiracetam was 0.89 ± 0.1, indicating high filter efficiency. Six of the 11 patients experienced concentrations outside the reported therapeutic range (12–46 mg/L). The average volume of distribution was 0.73 L/kg. CVVH clearance contributes a major fraction of the total levetiracetam clearance (36–73%) in neurocritically ill patients. The average bias and precision of the estimated vs. observed total clearance value was ~ 10.6% and 21.5%. Major dose determinants were identified to be SC and effluent flow rate. Patients with higher ultrafiltrate rates will have increased drug clearance and, therefore, will require higher doses in order to match exposures seen in patients with normal renal function.